2016
DOI: 10.21829/myb.2008.1411221
|View full text |Cite
|
Sign up to set email alerts
|

Anatomía de la madera de cinco especies de la familia Rosaceae

Abstract: RESUMENSe presenta la descripción anatómica, de tipo macroscópica y microscópica de la madera de cinco especies de frutales que pertenecen a la familia Rosaceae. Las especies recolectadas fueron:subfamilia Prunoideae. La colecta se hizo en el estado de Puebla, en el municipio de San Felipe Teotlalcingo. Se muestreó un ejemplar por especie. Para el estudio macroscópico se usaron muestras de 15 x 7 x 1 cm y para el microscópico se hicieron laminillas fijas de cortes y de material disociado. Se obtuvieron tablill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Thus, apricot wood has shorter cell dimensions compared to peach, apple, pear, and cherry. Evaluation of the wood anatomy of five Rosaceae family species showed that it could be potentially be used at the end of fruit production 20 . Modern, efficient wood machine processing allows interesting material to be obtained from any wood, including the short trunks of apricot trees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, apricot wood has shorter cell dimensions compared to peach, apple, pear, and cherry. Evaluation of the wood anatomy of five Rosaceae family species showed that it could be potentially be used at the end of fruit production 20 . Modern, efficient wood machine processing allows interesting material to be obtained from any wood, including the short trunks of apricot trees.…”
Section: Introductionmentioning
confidence: 99%
“…Orchards could also be ‘exploited’ as starting material through extracting secondary metabolites with high intrinsic value, due to their wide range of biological activities. For instance, several studies have demonstrated the potential uses of the secondary metabolites derived from agricultural wood extracts, including antioxidant compounds present in vineyard wood, 21 and the radical scavenging properties of extracts derived from olive tree wood 20 …”
Section: Introductionmentioning
confidence: 99%